2017
DOI: 10.1111/ced.13215
|View full text |Cite
|
Sign up to set email alerts
|

Fever, lipodystrophy and cutaneous lesions

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Eleven studies reported the results of skin biopsy. 6,9,14,15,[18][19][20][22][23][24][25] The main findings of these biopsies were interstitial and perivascular infiltrate with one of these cells or mixed of them; histiocytic, lymphocytic, polymorphonuclear, atypical/typical mononuclear, or eosinophilic cells. Langerhans cells were also reported in some cases, but mature neutrophils were the most reported ones.…”
Section: Pathological Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies reported the results of skin biopsy. 6,9,14,15,[18][19][20][22][23][24][25] The main findings of these biopsies were interstitial and perivascular infiltrate with one of these cells or mixed of them; histiocytic, lymphocytic, polymorphonuclear, atypical/typical mononuclear, or eosinophilic cells. Langerhans cells were also reported in some cases, but mature neutrophils were the most reported ones.…”
Section: Pathological Findingsmentioning
confidence: 99%
“…Nine studies mentioned the results of the bone marrow, and they were mostly normal. 1,2,9,15,19,20,[22][23][24] However, in a few cases, the specimen demonstrated one of these findings; trilineage hematopoiesis with normal cytogenetic evaluation, increased erythropoiesis, reactive changes, infiltration of immature neutrophils/myeloid precursors, and atypical mononuclear cells that were most likely activated macrophages (positive for CD68 and CD163).…”
Section: Pathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation